Application Of The Problem Based Learning Model For Improving Mathematics Learning Outcomes In Elementary School V Class Students - Syamsiah Djaga; Latri Latri; Ria Fadillah (International Journal of Elementary School Teacher, 2022)
This study examines the low learning outcomes of mathematics in fifth grade students of SD Inpres Maccini Baru, Tamalate District, Makassar City. The purpose of this study was to describe the application of the Problem Based Learning model to improve mathematics learning outcomes in fifth grade students of SD Inpres Maccini Baru, Tamalate District, Makassar City. This study uses a descriptive qualitative approach. The type of research is classroom action research (CAR) which is carried out in 4 (four) stages in each cycle, namely planning, implementation, observation, and reflection. The focus of this research is the application of the Problem Based Learning model and student learning outcomes. The setting of this research is the fifth grade of SD Inpres Maccini Baru, Tamalate District, Makassar City, while the subject of this research is one class teacher and 24 students consisting of 13 female students and 11 male students. In this study, the researcher acts as a teacher and the class teacher acts as an observer. Data analysis techniques are qualitative and quantitative. The results showed that the teacher's teaching activities in the first cycle still showed a sufficient category and in the second cycle increased to a good category. Similarly, student learning activities in the first cycle were in the sufficient category and in the second cycle increased to a good category. Meanwhile, student learning outcomes in the first cycle were in the sufficient category and student learning outcomes in the second cycle increased to a good category. The conclusion of this study is that through the application of the Problem Based Learning model, the learning outcomes of mathematics in fifth grade students of SD Inpres Maccini Baru, Tamalate District, Makassar City have increased.